THE EFFECT OF TASK BASED LEARNING ON STUDENTS’ ACHIEVEMENT IN WRITING NARRATIVE TEXT - Afsyah Tri Mida Sari; Sumarsih - - (TRANSFORM : Journal of English Language Teaching and Learning, 2014)
Abstract This study deals with The Effect of Task Based Learning Strategy on Students’ achievement in Writing Narrative text. The strategy of this research was experimental research. The population of the research was nine parallel classes of the eleventh grade of SMA NEGERI 11 MEDAN totaling students 362 students. 20 percent of totaling students were taken out as the sample of experimental group and the control group by using random sampling technique. The data were collected by conducting an essay test of writing. The result of the test was analyzed statistically by applying the t-test formula. From the calculation, it was obtained that tobserved (3.529) higher that ttable (1.993) at the level of significance (α = 0.05) and df = 72. It means that the application of Task Based Learning Strategy on Students’ Achievement in writing Narrative Text was effective because the result showed that students’ score were higher after the treatment. In conclusion, it is acceptable that Task based learning Strategy gave a significance effect on students’ achievement in writing narrative story.   Key words: Task Based Learning Strategy, writing Achievement, Narrative Text